Social risk factors for speech, scholastic and coordination disorders: a nationwide register-based study - Bianca Arrhenius; David Gyllenberg; Roshan Chudal; Venla Lehti; Minna Sucksdorff; Ona Sourander; Juha-Pekka Virtanen; Jutta Torsti; Andre Sourander (BMC Public Health, 2022)
Background
Broadly defined learning and coordination disorders (LCDs) are common in the population and have previously been associated with familial social risk factors and male sex. However, comprehensive nationwide studies of these risk factors in LCD subgroups are lacking. Our objective was to assess different LCDs in relation to sex and maternal education, marital status and socioeconomic status based on occupation.
Methods
We conducted a nationwide register-based study. The following diagnoses were identified from the Finnish Hospital Discharge Register (FHDR) according to the ICD-10 (n = 28,192): speech disorders (F80), scholastic disorders (F81), motor and coordination disorders (F82) and mixed developmental disorder (F83). To study cumulative incidence and male: female ratios of service use of LCDs, we used a cohort design among all Finnish children born singleton 1996–2007 (n = 690,654); to study social risk factors, we used a nested case-control design with extensive register data on both cases and matched controls (n = 106,616).
Results
The cumulative incidence was 4.7% for any LCD by age 15 and the changes in cumulative incidence over time were minor. The male: female ratios were 2.2–3.0 across LCD subgroups. Learning and coordination disorders were more common in households with lower maternal education, socioeconomic status based on occupation and among children with single mothers at the time of birth; the odds ratios (OR) for any LCD were 1.2–1.9 across risk factors. The odds for LCD diagnosis increased linearly with the number of social risk factors, except for coordination disorder. The effect size of three risk factors was highest in the group with mixed or multiple LCDs; OR 3.76 (95% CI 3.31–4.28).
Conclusions
Multiple social risk factors increase the odds for multiple, more comprehensive learning difficulties. The findings have implications for service planning, as early identification and interventions of learning and coordination disorders might reduce related long-term social adversities.